2017
DOI: 10.1111/bju.13827
|View full text |Cite
|
Sign up to set email alerts
|

Hospital volume and perioperative outcomes for radical cystectomy: a population study

Abstract: Objectives To evaluate the association between hospital volume and perioperative outcomes of radical cystectomy (RC) using state population data for a contemporary Australian cohort. Patients and Methods Patients undergoing RC for urothelial malignancy in the state of Victoria, Australia between July 2003 and June 2014 were identified using the Victorian Admitted Episodes Dataset (VAED). Hospitals were divided into tertiles according to their caseload per year. Hospitals performing <4 RCs/year were defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 44 publications
1
21
1
Order By: Relevance
“…In keeping with our results, one previous Australian study of 804 RC patients reported no significant difference in risk of 30‐ and 90‐day mortalities among high‐volume (≥7 RCs/year) versus moderate‐volume (4–6/year) and low‐volume (≤3/year) hospitals following adjustment for casemix . A further state‐based Australian study ( n = 803 patients), did, however, report a significantly increased risk of in‐hospital mortality following RC at low‐volume hospitals (<4/year) . We conducted additional analyses using various hospital volume categories but found no association between hospital volume and any outcome.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In keeping with our results, one previous Australian study of 804 RC patients reported no significant difference in risk of 30‐ and 90‐day mortalities among high‐volume (≥7 RCs/year) versus moderate‐volume (4–6/year) and low‐volume (≤3/year) hospitals following adjustment for casemix . A further state‐based Australian study ( n = 803 patients), did, however, report a significantly increased risk of in‐hospital mortality following RC at low‐volume hospitals (<4/year) . We conducted additional analyses using various hospital volume categories but found no association between hospital volume and any outcome.…”
Section: Discussionsupporting
confidence: 78%
“…Other population‐based studies have reported in‐hospital mortality rates of around 2.0–3.5% and 30‐day mortality between 3.0% and 5.5% . One previous Australian state‐based study reported an in‐hospital mortality rate of 2.2% . While overall the number of in‐hospital, 30‐ and 90‐day deaths over the 15 years of the study were relatively few, we did observe a reduction in deaths over time despite a significant increase in the number of RCs over the same period.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…If we go to other less selected settings, things start to change. An Australian epidemiologic study has observed a 2.2% rate after 803 surgeries (15). A British study evaluated 15,292 patients and have observed a mortality rate of 2.7% after 30 days and of 7% after 90 months (12).…”
Section: High Mortality Rates After Radical Cystectomy: We Must Have mentioning
confidence: 99%
“…The use of haematuria clinics is still in its infancy in our region but other measures may also be utilised to avoid delays in definitive treatments. The concept of surgeon and hospital volume is also explored . The number of cystectomies per centre is certainly lower than what is considered ‘high volume’ in Europe – as always the focus must be on outcomes.…”
mentioning
confidence: 99%